CHALLENGES AND PROSPECTS OF COOPERATION BETWEEN RUSSIAN COMMERCIAL BANKS AND OVERSEAS BANKS - Yuliya N. Severina (Plekhanov Russian University of Economics, 2017)
The article deals with researching the work of credit organizations with participation of non-residents in Russia today and prospects of the development of home bank sector. Advantages of foreign banks functioning on Russian market are shown. Problems hindering the process of consolidation and development of interbank interaction were identified. Findings of the research allow us to conclude that it is next to impossible to expect a fast growth of European and American banks on Russian market or arrival of new players. At the same time a sharp reduction in functioning of overseas banks in Russia is hardly probable. Due to the intention of Russia to expand cooperation with Asian countries these banks' arrival is feasible.